Numerical simulations help revealing the dynamics underneath the clouds of Jupiter - Johannes Wicht (Nature Portfolio, 2020)
Since its arrival at Jupiter in 2016, NASA’s Juno spacecraft has been performing high-precision measurement of the gravity and magnetic fields. When combined with numerical simulations, they provide a unique window to the dynamics in the planet’s deep atmosphere.